Annie Leibovitz at work - Leibovitz, Annie 1949- (Random House, 2008)
From the Publisher: Annie Leibovitz describes how her pictures were made, starting with Richard Nixon's resignation, a story she covered with Hunter S. Thompson, and ending with Barack Obama's campaign. In between are a Rolling Stones Tour, John Lennon and Yoko Ono, Demi Moore, Whoopi Goldberg, The Blues Brothers, Arnold Schwarzenegger, Keith Haring, Mikhail Baryshnikov, Patti Smith, George W. Bush, William S. Burroughs, Kate Moss and Queen Elizabeth. The most celebrated photographer of our time discusses portraiture, reportage, fashion photography, lighting, and digital cameras.
Nixon's resignation -- The Rolling Stones -- John and Yoko -- Conceptual pictures -- Advertising -- Al Sharpton -- Arnold Schwarzenegger -- Dance -- Demi Moore -- Performance -- Peak performance -- War -- O. J. Simpson -- Impromptu -- Patti Smith -- Fashion -- Nudes -- Groups -- Presence and charisma -- Being there -- My mother -- Sarah -- Susan -- Hollywood -- The Queen -- The process -- The road West -- Ten most-asked questions
Keywords: Leibovitz, Annie / 1949-; Leibovitz, Annie <1949->; Leibovitz, Annie -- 1949-; Geschichte 1972-2008; Portrait photography; Photography, Artistic; Celebrities / Portraits; Celebrities -- Portraits; Porträtfotografie; Berühmte Persönlichkeit; Fotografie; Bildband